Transbronchial cryobiopsies for diagnosing interstitial lung disease: real-life experience from a tertiary referral center for interstitial lung disease - Wälscher, Julia; Groß, Benjamin; Eberhardt, Ralf; Heußel, Claus Peter; Eichinger, Monika; Lasitschka, Felix; Herth, Felix; Kreuter, Michael (Respiration, 2019)
BACKGROUND: Transbronchial cryobiopsy (cTBB) may offer an alternative to surgical lung biopsy (SLB) for histopathological diagnosis of interstitial lung diseases (ILDs). However, real-life experience is limited, although case series are increasingly reported. - OBJECTIVES: We aimed to evaluate the value of cTBB performed under real-life conditions in a tertiary care center for ILDs. - METHODS: Data on all patients undergoing a cTBB for evaluation of suspected ILD between October 2015 and January 2017 were included in this retrospective case series. Procedure details, complication rates, histopathological results, and diagnostic consensus reached by a multidisciplinary team (MDT) discussion were collated and evaluated. - RESULTS: A total of 109 patients (mean age 64 years, range 19-85; 66% male, 38% never smokers) referred to our center with features suggestive of ILD underwent cTBB. The mean FVC% predicted was 77% (range 41-131), with a mean DLCO of 51% (range 20-86), and a 6-min walking test (6MWT) of 402 m (range 100-642). On average, 4 samples were taken from each patient (range 1-8), with a mean biopsy diameter of 5 mm (range 2-12). Complications included pneumothorax (11.9%), all treated with chest drain. Moderate bleeding occurred in 28.4% (all resolved without active measures). No acute disease exacerbations and no deaths occurred. A histopathological pattern diagnosis was possible in 80 cases (73.4%), and 26.6% of cases were considered nonspecific. An MDT consensus diagnosis was reached in 83.5% of cases. Subsequent SLB was proposed in 13 cases and performed in 8 cases. - CONCLUSIONS: In the real-world setting, cTBB has a meaningful diagnostic value in the context of a MDT approach and may enable histopathological assessment even in patients with more advanced disease unsuitable for SLB.
Gesehen am 26.04.2019